2017
DOI: 10.1016/j.plaphy.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Functional regulation of ginsenoside biosynthesis by RNA interferences of a UDP-glycosyltransferase gene in Panax ginseng and Panax quinquefolius

Abstract: Panax ginseng (Asian ginseng) and Panax quinquefolius (American ginseng) have been used as medicinal and functional herbal remedies worldwide. Different properties of P. ginseng and P. quinquefolius were confirmed not only in clinical findings, but also at cellular and molecular levels. The major pharmacological ingredients of P. ginseng and P. quinquefolius are the triterpene saponins known as ginsenosides. The P. ginseng roots contain a higher ratio of ginsenoside Rg1:Rb1 than that in P. quinquefolius. In gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 26 publications
(53 reference statements)
0
40
0
Order By: Relevance
“…The identity of UGTPg45 and PgUGT74AE2 was 95.4%, while the identity of UGTPg29 and PgUGT94Q2 was 99.77%. Lu et al [ 47 ] cloned and identified a UGT gene named Pq3-O-UGT2 from P. quinquefolius . In vitro enzymatic assay confirmed that Pq3-O-UGT2 catalyzed the glycosylation of Rh2 and F2 to produce Rg3 and Rd.…”
Section: Udp-glycosyltransferasementioning
confidence: 99%
“…The identity of UGTPg45 and PgUGT74AE2 was 95.4%, while the identity of UGTPg29 and PgUGT94Q2 was 99.77%. Lu et al [ 47 ] cloned and identified a UGT gene named Pq3-O-UGT2 from P. quinquefolius . In vitro enzymatic assay confirmed that Pq3-O-UGT2 catalyzed the glycosylation of Rh2 and F2 to produce Rg3 and Rd.…”
Section: Udp-glycosyltransferasementioning
confidence: 99%
“…Five UGTs were identified from P. ginseng , including UGTPg1, UGTPg100, UGTPg101, PgUGT94Q2 and PgUGT74AE2. PgUGT74AE2 can catalyze the glycosylation of C3-OH of protopanaxadiol and compound K to form ginsenoside Rh2 and F2, respectively [24]; PgUGT94Q2 can catalyze Rh2 and F2 to form Rg3 and Rd., respectively, by forming a β-1,2-glycosidic linkage [24, 25]; UGTPg1 was characterized to glycosylate the C20-OH of PPD and PPT to produce compound K and ginsenoside F1, respectively [26]; UGTPg101 can catalyze the glycosylation of C20-OH of PPT and C6-OH of F1 to produce F1 and Rg1, respectively [27]; UGTPg100 can catalyze the glycosylation of C6-OH of PPT and F1 to form ginsenoside Rh1 and Rg1, respectively [27]. Transcription factors (TFs) play crucial roles in the regulation of secondary metabolite biosynthesis [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al 2017 [59] Panax quinquefolius Biosynthesis of protopanaxadiol-group ginsenosides UDP-glucosyltransferase gene RNA interference Lu et al 2017 [60] Panax quinquefolius Ginsenoside synthesis Down-regulation of UDP-Glycosyltransferase gene RNA interference Lu et al 2017 [61] Papaver somniferum Salutaridinol 7-O-acetyltransferase (SalAT)…”
Section: Agrobacterium-mediated Transformationmentioning
confidence: 99%